P2X7 receptor restrains pathogenic Tfh cell generation in systemic lupus erythematosus - Faliti, Caterina E.; Gualtierotti, Roberta; Rottoli, Elsa; Gerosa, Maria; Perruzza, Lisa; Romagnani, Andrea; Pellegrini, Giovanni; De Ponte Conti, Benedetta; Rossi, Riccardo L.; Idzko, Marco; Mazza, Emilia M.C.; Bicciato, Silvio; et al. (The Journal of experimental medicine, 2019)
Altered control of T follicular helper (Tfh) cells can lead to generation of autoantibodies and autoimmune manifestations. Signaling pathways that selectively limit pathogenic responses without affecting the protective function of Tfh cells are unknown. Here we show that the ATP-gated ionotropic P2X7 receptor restricts the expansion of aberrant Tfh cells and the generation of self-reactive antibodies in experimental murine lupus, but its activity is dispensable for the expansion of antigen-specific Tfh cells during vaccination. P2X7 stimulation promotes caspase-mediated pyroptosis of Tfh cells and controls the development of pathogenic ICOS+ IFN-γ–secreting cells. Circulating Tfh cells from patients with systemic lupus erythematosus (SLE) but not primary antiphospholipid syndrome (PAPS), a nonlupus systemic autoimmune disease, were hyporesponsive to P2X7 stimulation and resistant to P2X7-mediated inhibition of cytokine-driven expansion. These data point to the P2X7 receptor as a checkpoint regulator of Tfh cells; thus, restoring P2X7 activity in SLE patients could selectively limit the progressive amplification of pathogenic autoantibodies, which deteriorate patients’ conditions.